ANALYSIS AND CHOICE OF CALCULATION METHODS OF EFFICIENCY OF THE FUEL BURNING IN OPEN GAS FURNACES - I. A. Trusova; D. V. Mendelev; S. V. Korneev; P. E. Ratnikov (Литьë и металлургия)
The analysis of calculation methods of efficiency of the fuel burning in open gas furnaces is given. The norms of consumption of certain types of energy fo r output of products volume are determined.